The role of Block-Chain in Cloud-based IoT solutions to build end-to-end automated and secured solutions - Mukunthan, B; Govindaraju, S; Komagal Yallini, S.K; VibinChander, S; RanjithKumar, C (International Journal of Computer Sciences and Engineering, 2020)
Block-Chain is referred as the list of transactions stored in multiple participating servers rather than on a central transaction server. Each and every participant in the Block-Chain network is granted access to an up-to-date copy of this encrypted catalog so they can read, write, and validate transactions. Block-Chains have recently gained a lot of attention in IoT solutions even though they are used mostly in the financial domain. Block-Chain can relatively support in accomplishing the vision of distributed IoT, facilitating transactions and coordination among interacting devices. The two technologies Block- Chain and IoT are used to build end to end automated and secured solutions. Internets of things (IoT) solutions are being effectively implemented in many different sectors, such as healthcare, warehousing, transportation, and logistics. Current unified, Cloud-based IoT solutions may not gauge and meet the network security defies faced by large-scale enterprises. The use of Block-Chain as a distributed catalog of transactions and peer-to-peer communication among contributing nodes can unravel such problems. This paper gives an idea of Block-Chain-enabled IoT solutions and shows how to use the Block-Chain platform for an IoT application in a multi partner environment.